MARKER ASSISTED BREEDING WITHOUT BACKGROUND SELECTION FOR IMPROVEMENT OF DROUGHT TOLERANCE IN A BREAD WHEAT CULTIVAR - AMARDEEP* and T. SINGH, (The Journal of Research ANGRAU, 2020)
Drought stress is a major limiting factor in wheat production. The study was conducted duringrabi crop seasons from 2010-11 to 2019-20 by utilizing a marker-assisted selection scheme tointrogress a major drought insensitive yield QTL (Qyld.csdh.7AL) from SQ1 into Indian wheat cultivar(HD2967) using SSR marker Xwmc273.3, leading to the development of 3 improved wheat lineshaving relatively higher grain yield under water stress condition. HD2967, a high yielding wheat cultivarwhich has been proved as a successful variety for northwestern plain zone (NWPZ) of India butsensitive to drought stress, was used as the recurrent parent. For introgression of this major yieldQTL, a cross between HD2967 and SQ1 was made and subsequently two back crosses with recurrentparent (HD2967) were attempted during the off/crop seasons. QTL was validated in the BC1F2population using foreground selection followed by the collection of phenotypic data (grain weight/ear,grain weight/plant, plant biomass, flag leaf chlorophyll content, and harvest index) of two groups ofplants having SQ1 and HD2967 alleles for the QTL. After foreground and phenotypic selection,homozygous superior lines containing the SQ1 allele for the QTL Qyld.csdh.7AL were selected inBC2F4 population. The high yield in the selected plants was attributed to grain weight/plant, biomass/plant, and flag leaf chlorophyll content.